Testing a Distributed System. - MADDOX, PHILIP (Communications of the ACM, 2015)
The article presents general strategies for testing distributed computing systems and specific strategies for testing distributed data storage systems. These systems have three parts. One part collects data, one part collates all of the data into consistent messages, and another part stores the data for later retrieval. According to the author, if one cannot co-locate processes on the same box, one may run them in virtual machines, which provides much of the same functionality one gets by running them on the same machine.